Ion-synergetic high-performance sodium ion battery positive electrode material and preparation method thereof

The ionic coordination method is prepared to prepare sodium ion battery ion battery materials with a single tunnel -type structure, solving the problem of existing positive electrode materials in the charging and discharge capacity, multiplier performance and cycle stability, and realize high -performance sodium ion battery positive poles.

CN119361675APending Publication Date: 2025-01-24LIAOCHENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411521780.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have problems such as low charge and discharge capacity and poor cycle stability, especially the excessive layered structure will reduce the rate performance and cycle stability of the battery.

Method used

A transition metal oxide cathode material with a single tunnel microstructure is prepared through an ion synergy method. The specific molecular formula is NaxMn1-yTyO2-zNz, where T and N are nickel and fluorine elements respectively, 0.44≤x≤0.6, 0≤ y≤0.3, 0≤z≤0.3, and y and z are not 0 at the same time. The material is prepared through a sintering process and has excellent rate performance and long cycle life.

Benefits of technology

It achieves high charge and discharge capacity, excellent rate performance and long cycle life, and solves the shortcomings of existing cathode materials in cycle stability and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361675A_ABST
    Figure CN119361675A_ABST
Patent Text Reader

Abstract

The invention relates to the field of preparation of sodium-ion battery positive electrode materials, and particularly discloses an ion-synergetic high-performance sodium-ion battery positive electrode material and a preparation method thereof. The molecular formula of the positive electrode material is Na < x > Mn < 1-y > Ty < y > O < 2-z > N < z >, wherein T and N are nickel and fluorine elements respectively. 0.44 < = x < = 0.6, 0 < = y < = 0.3, 0 < = z < = 0.3, and y and z are not 0 at the same time. A manganese-based oxide material with a single tunnel-type structure is jointly constructed by Na, Mn, T, O and N, the appearance of the positive electrode material is of a uniform rod-shaped structure, the introduced T and N are important bases for realizing the single tunnel-type structure, sodium ion storage active sites are increased, the average valence state of manganese ions is improved, the stability of a lattice structure is enhanced, and the positive electrode material can be used for preparing a lithium ion battery. And the sodium ion migration dynamic behavior is enhanced, so that the positive electrode material has high charge-discharge capacity, excellent rate capability and long cycle life / high cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of positive electrode materials for sodium ion batteries, and in particular to an ion-synergistic high-performance positive electrode material for sodium ion batteries and a preparation method thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not be necessarily regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.

[0003] The positive electrode materials of sodium ion batteries mainly include transition metal oxides, Prussian blue compounds, organic compounds and polyanion compounds. Among the above-mentioned positive electrode materials for sodium ion batteries, tunnel-type transition metal oxide positive electrode materials have the advantages of excellent structural stability and fast sodium ion migration channels. However, this material has the problem of low charge and discharge capacity. Currently, researchers use ion doping, coating and other methods to regulate the micro-nano structure of positive electrode materials. Although the charge and discharge capacity of positive electrode materials can be improved, the transition metal oxide positive electrode materials obtained by this method usually have both tunnel and layered two-phase structures. If there are too many layered structures in the positive electrode material, the cycle stability and rate performance of the sodium ion battery will be seriously reduced. Summary of the invention

[0004] In view of the above problems, the present invention provides an ion-synergistic high-performance sodium ion battery positive electrode material and a preparation method thereof, wherein the prepared transition metal oxide positive electrode material has a single tunnel-type microstructure, and a sodium ion battery positive electrode material having high charge and discharge capacity, excellent rate performance and long cycle life is obtained. Specifically, the technical solution of the present invention is as follows.

[0005] First, the present invention provides an ion-synergistic high-performance sodium ion battery positive electrode material, the molecular formula of which is Na x Mn 1-y T y O 2-z N z , wherein: T and N are nickel (Ni) and fluorine (F) elements respectively. 0.44≤x≤0.6, 0≤y≤0.3, 0≤z≤0.3, and y and z are not 0 at the same time. The positive electrode material has a unique and single tunnel structure, and has high charge and discharge capacity, excellent rate performance and long cycle life / high cycle stability.

[0006] Secondly, the present invention discloses a method for preparing the ion-synergistic high-performance sodium ion battery positive electrode material, comprising the following steps: (1) According to the Na x Mn 1-y Ty O 2-z N z The atomic ratio of Na, Mn, T and / or N elements in the raw materials is determined by weighing the sodium source, manganese source, T source and / or N source. Then, each raw material is dissolved in an acidic solution and stirred for reaction, and the coprecipitated compound is separated, dried and ground to obtain a precursor for later use.

[0007] (2) Sintering the precursor in an oxygen-containing atmosphere to obtain the positive electrode material.

[0008] Furthermore, in step (1), the sodium source includes one or more of sodium carbonate, sodium acetate, sodium nitrate, sodium acetate, sodium oxalate, and sodium citrate. Preferably, since these sodium sources will volatilize during the high-temperature sintering process, 5-10% of the mass of the sodium source is added.

[0009] Furthermore, in step (1), the manganese source includes one or more of manganese sulfate, manganese acetate, manganese nitrate, and manganese acetate.

[0010] Furthermore, in step (1), the T source and the N source include one or more of nickel nitrate, nickel sulfate, nickel acetate, and sodium fluoride.

[0011] Furthermore, in step (1), the acidic solution comprises one or more of acetic acid and oxalic acid. Optionally, the concentration of the acidic solution is 1-5 mol / L, and the ratio of each raw material to the acidic solution is 1 g: 10-30 mL.

[0012] Furthermore, in step (1), the stirring reaction temperature is 50-80° C., and the reaction time is 4-6 hours. Optionally, the stirring rate is 120-500 rpm / min.

[0013] Furthermore, in step (1), the drying temperature is 100-120° C. and the drying time is 8-12 hours.

[0014] Furthermore, in step (1), the grinding speed is 200-450 rpm / min, the time is 0.2-2 h, and the ball-to-material ratio is 13-26:1.

[0015] Furthermore, in step (2), the sintering treatment temperature is 700-1000° C. and the time is 1-20 hours. Optionally, the oxygen-containing atmosphere includes air, etc.

[0016] Compared with the prior art, the present invention has the following beneficial technical effects: the present invention constructs a single tunnel-type microstructure through Na, Mn, O, T, and N. The appearance of the positive electrode material presents a uniform rod-like structure, wherein the introduced T and N are important foundations for realizing the single tunnel-type structure. At the same time, the active sites for sodium ion storage are increased, the average valence state of manganese ions is improved, the stability of the lattice structure is enhanced, and the sodium ion migration kinetic behavior is enhanced, so that the positive electrode material has high charge and discharge capacity, excellent rate performance, and long cycle life / high cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein: Figure 1 The X-ray diffraction patterns of the positive electrode materials prepared in the following Examples 1, 6, 8, 9 and 11.

[0018] Figure 2 (a) to (d) are SEM images of the microscopic morphology of the positive electrode materials prepared in the following Examples 6, 8, 9 and 11, respectively.

[0019] Figure 3 This is a rate performance test diagram of a sodium ion half-cell prepared using the positive electrode material of Example 9 below.

[0020] Figure 4 The long cycle performance test diagram of the sodium ion half-cell prepared with the positive electrode material of the following Example 9 at 1C.

[0021] Figure 5 This is a graph showing the long cycle performance of a sodium ion half-cell prepared with the positive electrode material of the following Example 9 at and 10C.

[0022] Figure 6 Cyclic voltammogram of a sodium ion half-cell prepared with the positive electrode material of Example 9 below at 0.2 mV / s.

[0023] Figure 7 Cyclic voltammogram of a sodium ion half-cell prepared for the positive electrode material of Example 11 below at 1 mV / s.

[0024] Figure 8 The capacity-voltage curve of a sodium ion full battery prepared with the positive electrode material of the following Example 9 at 0.1C.

[0025] Fig. 9 The long cycle performance diagram of the sodium ion full battery prepared with the positive electrode material of the following Example 9 at 1C. DETAILED DESCRIPTION

[0026] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0027] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If not otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. Now, the present invention is further described in conjunction with the accompanying drawings and specific embodiments of the present invention, and the preferred implementation methods and materials described in the present invention are only for demonstration purposes.

[0028] Example 1 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese and nickel elements of 0.44:0.95:0.05, weigh 1.5153 g of sodium acetate (5% excess sodium acetate), 5.7384 g of manganese sulfate and 0.3536 g of nickel acetate respectively, and slowly add them to 15 mL of oxalic acid solution (concentration of 2 mol / L) in sequence. Place them in a magnetic stirrer at a speed of 300 rap / min and stir thoroughly for 5 h at a stirring temperature of 60°C.

[0029] (2) The solid and liquid in (1) were separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor. (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 6 h. The temperature was then cooled to room temperature at a cooling rate of 10°C / min to obtain the positive electrode material Na 0.44 Mn 0.95 Ni 0.05 O2.

[0030] Example 2 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese and nickel of 0.44:0.9:0.1, weigh 1.5153 g of sodium acetate (5% excess of sodium acetate), 5.4364 g of manganese sulfate, and 0.7071 g of nickel acetate, respectively, and slowly add them to 15 mL of oxalic acid solution (concentration of 2 mol / L) in sequence. Place the mixture in a magnetic stirrer at a speed of 300 rap / min and stir thoroughly for 5 h at a stirring temperature of 60°C.

[0031] (2) The solid and liquid in (1) were separated by vacuum filtration. The obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor.

[0032] (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 6 h. The temperature was then cooled to room temperature at a cooling rate of 10°C / min to obtain the positive electrode material Na 0.44 Mn 0.9 Ni 0.1 O2.

[0033] Example 3 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese and nickel of 0.44:0.8:0.2, weigh 1.5153 g of sodium acetate (5% excess of sodium acetate), 4.8323 g of manganese sulfate, and 1.4142 g of nickel acetate, respectively, and slowly add them to 15 mL of oxalic acid solution (concentration of 5 mol / L) in sequence. Place the mixture in a magnetic stirrer at a speed of 300 rap / min and stir thoroughly for 5 h at a stirring temperature of 60°C.

[0034] (2) The solid and liquid in (1) were separated by vacuum filtration. The obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor.

[0035] (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 6 h. The temperature was then cooled to room temperature at a cooling rate of 10°C / min to obtain the positive electrode material Na 0.44 Mn 0.8 Ni 0.2 O2.

[0036] Example 4 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese and nickel of 0.44:0.7:0.3, weigh 1.5153 g of sodium acetate (5% excess of sodium acetate), 4.2282 g of manganese sulfate, and 2.1214 g of nickel acetate, respectively, and slowly add them to 15 mL of oxalic acid solution (concentration of 5 mol / L) in sequence. Place the mixture in a magnetic stirrer at a speed of 300 rap / min and stir thoroughly for 5 h at a stirring temperature of 60°C.

[0037] (2) The solid and liquid in (1) were separated by vacuum filtration. The obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor.

[0038] (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 6 h. The temperature was then cooled to room temperature at a cooling rate of 10°C / min to obtain the positive electrode material Na 0.44 Mn 0.7 Ni 0.3 O2.

[0039] Example 5 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese and fluorine of 0.44:1:0.1, weigh 1.5153 g of sodium acetate (5% excess of sodium acetate), 4.8323 g of manganese sulfate and 0.2879 g of sodium fluoride respectively, and slowly add them into 15 mL of oxalic acid solution (concentration of 1 mol / L) in sequence. Place them in a magnetic stirrer at a speed of 300 rap / min and stir thoroughly for 5 h at a stirring temperature of 60°C.

[0040] (2) The solid and liquid in (1) were separated by vacuum filtration. The obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor.

[0041] (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 6 h. The temperature was then cooled to room temperature at a cooling rate of 10°C / min to obtain the positive electrode material Na 0.44 MnO 1.9 F 0.1 .

[0042] Example 6 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese and fluorine of 0.44:1:0.2, weigh 1.5153 g of sodium acetate (5% excess of sodium acetate), 4.8323 g of manganese sulfate and 0.5759 g of sodium fluoride respectively, and slowly add them into 15 mL of oxalic acid solution (concentration of 2 mol / L) in sequence. Place them in a magnetic stirrer at a speed of 300 rap / min and stir thoroughly for 5 h at a stirring temperature of 60°C.

[0043] (2) The solid and liquid in (1) were separated by vacuum filtration. The obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor.

[0044] (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 6 h. The temperature was then cooled to room temperature at a cooling rate of 10°C / min to obtain the positive electrode material Na 0.44 MnO 1.8 F 0.2 .

[0045] Example 7 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese and fluorine of 0.44:1:0.3, weigh 1.5153 g of sodium acetate (5% excess of sodium acetate), 4.8323 g of manganese sulfate and 0.8639 g of sodium fluoride respectively, and slowly add them into 15 mL of oxalic acid solution (concentration of 2 mol / L) in sequence. Place them in a magnetic stirrer at a speed of 300 rap / min and stir thoroughly for 5 h at a stirring temperature of 60°C.

[0046] (2) The solid and liquid in (1) were separated by vacuum filtration. The obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor.

[0047] (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 6 h. The temperature was then cooled to room temperature at a cooling rate of 10°C / min to obtain the positive electrode material Na 0.44 MnO 1.7 F 0.3 .

[0048] Example 8 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese, nickel and fluorine of 0.44:0.95:0.05:0.1, weigh 1.5153 g of sodium acetate (5% excess of sodium acetate), 5.7384 g of manganese sulfate, 0.3536 g of nickel acetate and 0.2879 g of sodium fluoride respectively, add them slowly to 15 mL of oxalic acid solution (concentration of 2 mol / L) in sequence, place them in a magnetic stirrer at a speed of 300 rap / min, stir thoroughly for 4 h, and the stirring temperature is 80°C.

[0049] (2) The solid and liquid in (1) were separated by vacuum filtration. The obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor.

[0050] (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 6 h. The temperature was then cooled to room temperature at a cooling rate of 10°C / min to obtain the positive electrode material Na 0.44 Mn 0.95 Ni 0.05 O 1.9 F 0.1 .

[0051] Example 9 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese, nickel and fluorine of 0.44:0.8:0.2:0.1, weigh 1.5153 g of sodium acetate (5% excess of sodium acetate), 4.8323 g of manganese sulfate, 1.4142 g of nickel acetate and 0.2879 g of sodium fluoride respectively, add them slowly to 15 mL of oxalic acid solution (concentration of 2 mol / L) in sequence, place them in a magnetic stirrer at a speed of 300 rap / min, stir thoroughly for 5 h, and the stirring temperature is 60°C.

[0052] (2) The solid and liquid in (1) were separated by vacuum filtration. The obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor.

[0053] (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 6 h. The temperature was then cooled to room temperature at a cooling rate of 10°C / min to obtain the positive electrode material Na 0.44 Mn 0.8 Ni 0.2 O 1.9 F 0.1 .

[0054] Example 10 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese, nickel and fluorine of 0.44:0.9:0.1:0.2, weigh 1.5153 g of sodium acetate (5% excess of sodium acetate), 5.4364 g of manganese sulfate, 0.7071 g of nickel acetate and 0.5759 g of sodium fluoride respectively, add them slowly to 15 mL of oxalic acid solution (concentration of 2 mol / L) in sequence, place them in a magnetic stirrer at a speed of 300 rap / min, stir thoroughly for 6 h, and the stirring temperature is 50°C.

[0055] (2) The solid and liquid in (1) were separated by vacuum filtration. The obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor.

[0056] (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 6 h. The temperature was then cooled to room temperature at a cooling rate of 10°C / min to obtain the positive electrode material Na0.44 Mn 0.9 Ni 0.1 O 1.8 F 0.2 .

[0057] Embodiment 11 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium to manganese of 0.44:1, weigh 1.5153 g of sodium acetate (5% excess sodium acetate) and 6.0404 g of manganese sulfate, respectively, and slowly add them to 15 mL of oxalic acid solution (concentration of 2 mol / L), place it in a magnetic stirrer, rotate at 300 rap / min, stir thoroughly for 5 h, and the stirring temperature is 60°C; (2) The solid and liquid in (1) were separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor; (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 6 h. The temperature was then cooled to room temperature at a cooling rate of 10°C / min to obtain the positive electrode material Na 0.44 MnO2.

[0058] Example 12 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese, nickel and fluorine of 0.44:0.8:0.2:0.1, weigh 1.5875 g of sodium acetate (10% excess of sodium acetate), 4.8323 g of manganese sulfate, 1.4142 g of nickel acetate and 0.2879 g of sodium fluoride respectively, add them slowly to 15 mL of oxalic acid solution (concentration of 2 mol / L) in sequence, place them in a magnetic stirrer at a speed of 300 rap / min, stir thoroughly for 5 h, and the stirring temperature is 60°C.

[0059] (2) The solid and liquid in (1) were separated by vacuum filtration. The obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor.

[0060] (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 6 h. The temperature was then cooled to room temperature at a cooling rate of 10°C / min to obtain the positive electrode material Na 0.44 Mn 0.8 Ni 0.2 O 1.9 F 0.1 .

[0061] Example 13 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese, nickel and fluorine of 0.44:0.8:0.2:0.1, weigh 1.5153 g of sodium acetate (5% excess of sodium acetate), 4.8323 g of manganese sulfate, 1.4142 g of nickel acetate and 0.2879 g of sodium fluoride respectively, add them slowly to 15 mL of oxalic acid solution (concentration of 2 mol / L) in sequence, place them in a magnetic stirrer at a speed of 300 rap / min, stir thoroughly for 5 h, and the stirring temperature is 60°C.

[0062] (2) The solid and liquid in (1) were separated by vacuum filtration. The obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor.

[0063] (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 700°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 6 h. Then, the temperature was cooled to room temperature at a cooling rate of 10°C / min and taken out to obtain the positive electrode material Na 0.44 Mn 0.8 Ni 0.2 O 1.9 F 0.1 .

[0064] Embodiment 14 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese, nickel and fluorine of 0.44:0.8:0.2:0.1, weigh 1.5153 g of sodium acetate (5% excess of sodium acetate), 4.8323 g of manganese sulfate, 1.4142 g of nickel acetate and 0.2879 g of sodium fluoride respectively, add them slowly to 15 mL of oxalic acid solution (concentration of 2 mol / L) in sequence, place them in a magnetic stirrer at a speed of 300 rap / min, stir thoroughly for 5 h, and the stirring temperature is 60°C.

[0065] (2) The solid and liquid in (1) were separated by vacuum filtration. The obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor.

[0066] (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 1000°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 6 h. Then, the temperature was cooled to room temperature at a cooling rate of 10°C / min and taken out to obtain the positive electrode material Na 0.44 Mn 0.8 Ni 0.2 O 1.9 F 0.1 .

[0067] Embodiment 15 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese, nickel and fluorine of 0.44:0.8:0.2:0.1, weigh 1.5153 g of sodium acetate (5% excess of sodium acetate), 4.8323 g of manganese sulfate, 1.4142 g of nickel acetate and 0.2879 g of sodium fluoride respectively, add them slowly to 15 mL of oxalic acid solution (concentration of 2 mol / L) in sequence, place them in a magnetic stirrer at a speed of 300 rap / min, stir thoroughly for 5 h, and the stirring temperature is 60°C.

[0068] (2) The solid and liquid in (1) were separated by vacuum filtration. The obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor.

[0069] (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 1 h. Then, the temperature was cooled to room temperature at a cooling rate of 10°C / min and taken out to obtain the positive electrode material Na0.44 Mn 0.8 Ni 0.2 O 1.9 F 0.1 .

[0070] Example 16 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese, nickel and fluorine of 0.44:0.8:0.2:0.1, weigh 1.5153 g of sodium acetate (5% excess of sodium acetate), 4.8323 g of manganese sulfate, 1.4142 g of nickel acetate and 0.2879 g of sodium fluoride respectively, add them slowly to 15 mL of oxalic acid solution (concentration of 2 mol / L) in sequence, place them in a magnetic stirrer at a speed of 300 rap / min, stir thoroughly for 5 h, and the stirring temperature is 60°C.

[0071] (2) The solid and liquid in (1) were separated by vacuum filtration. The obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor.

[0072] (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 20 h. Then, the temperature was cooled to room temperature at a cooling rate of 10°C / min and taken out to obtain the positive electrode material Na 0.44 Mn 0.8 Ni 0.2 O 1.9 F 0.1 .

[0073] Embodiment 17 A method for preparing an ion-synergistic high-performance sodium ion battery positive electrode material comprises the following steps: (1) According to the atomic ratio of sodium, manganese, nickel and fluorine of 0.44:0.8:0.2:0.1, weigh 1.5153 g of sodium acetate (5% excess of sodium acetate), 4.8323 g of manganese sulfate, 1.4142 g of nickel acetate and 0.2879 g of sodium fluoride respectively, add them slowly to 15 mL of acetic acid solution (concentration of 2 mol / L) in sequence, place them in a magnetic stirrer at a speed of 300 rap / min, stir thoroughly for 5 h, and the stirring temperature is 60°C.

[0074] (2) The solid and liquid in (1) were separated by vacuum filtration. The obtained solid was placed in a forced air drying oven and dried at 100°C for 12 h. The dried sample was ground by ball milling with a ball-to-material ratio of 20:1, a ball milling speed of 300 rpm / min, and a ball milling time of 0.5 h to obtain a uniform precursor.

[0075] (3) The precursor powder obtained in (2) was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 6 h. The temperature was then cooled to room temperature at a cooling rate of 10°C / min to obtain the positive electrode material Na 0.44 Mn 0.8 Ni 0.2 O 1.9 F 0.1 .

[0076] 1. Figure 1 1 is the X-ray diffraction pattern of the positive electrode materials prepared in Example 1, Example 6, Example 8, Example 9 and Example 11. As can be seen from the figure, the peak positions of the diffraction peaks of Example 1, Example 6, Example 8 and Example 9 are similar to those of the tunnel-type transition metal oxide Na 0.44 The peak positions of MnO2 are basically consistent, all belonging to the orthorhombic system and the Pbam space group, indicating that the positive electrode materials prepared in Examples 1, 6, 8, and 9 present a unique tunnel-type structure.

[0077] 2. Figure 2 (a) to (d) are respectively SEM images of the microscopic morphology of the positive electrode materials prepared in Example 6, Example 8, Example 9 and Example 11. As can be seen from the figures, these positive electrode materials all present a relatively regular rod-like structure, and the particle size is relatively uniform, about 6 to 10 μm in length and about 3 to 6 μm in width.

[0078] 3. Electrochemical performance test: (1) Assembly of button sodium ion half-cell: Weigh 0.064 g of the positive electrode material prepared in Examples 1 to 17, 0.008 g of the conductive agent (Super P), and 0.004 g of the binder (polyvinylidene fluoride), respectively, and evenly disperse them in 2 mL of N-methylpyrrolidone to form an electrode slurry. The slurry is evenly coated on aluminum foil, and the electrode is placed in a vacuum drying oven at 100°C for 12 h, and then cut into a circular positive electrode sheet with a diameter of 12 mm by a roller machine and a slicer. In an inert gas glove box (H2O≤0.01ppm, O2≤0.01ppm), a metal sodium sheet with a diameter of 14mm and a thickness of 0.2mm was used as the negative electrode, a 12mm circular electrode sheet was used as the positive electrode, Whatman's GF / F was used as the separator, and 1mol / L sodium perchlorate was dissolved in ethylene carbonate and propylene carbonate (1:1Vol% containing 5% fluoroethylene carbonate) as the electrolyte to assemble a CR2032 button half-cell. For the charge and discharge test of the above button half-cell, the test voltage range was 2~4V, and the current density was 1C=120mA / g.

[0079] (2) Assembly of button sodium-ion full battery: The preparation process of the positive electrode sheet is as described in (1) above. The hard carbon negative electrode was prepared as follows: 0.08 g of Kuraray hard carbon (Type 2), 0.01 g of conductive agent Super P, and 0.01 g of binder sodium hydroxymethyl cellulose were weighed, and the above materials were evenly dispersed in 2 mL of deionized water to form an electrode slurry, which was evenly coated on an aluminum foil. The electrode was placed in a vacuum drying oven and dried at 100°C for 12 h. After being rolled by a roller machine, it was cut into a circular negative electrode with a diameter of 12 mm by a slicer. In an inert gas glove box (H2O≤0.01 ppm, O2≤0.01 ppm), the above circular electrode was used as the negative electrode, the circular electrode in (1) was used as the positive electrode, Whatman's GF / F was used as a separator, and 1 mol / L sodium perchlorate was dissolved in ethylene carbonate and propylene carbonate (1:1 Vol% containing 5% fluoroethylene carbonate) as an electrolyte to assemble a CR2032 button-type sodium ion full battery. For the above button full battery charge and discharge test, the test voltage range is 1.5~4V, and the current density is 1C=120mA / g.

[0080] Figure 3The rate performance test diagram of the sodium ion half-cell prepared from the positive electrode material of Example 9. The average charge / discharge specific capacities at current densities of 0.1, 0.2, 0.5, 1, 2, 5 and 10C are 132.1 / 131.4 mAh / g, 129.4 / 129.3 mAh / g, 126.2 / 126 mAh / g, 123.2 / 123 mAh / g, 118.2 / 118.1 mAh / g, 105.2 / 104.9 mAh / g and 87.4 / 87.2 mAh / g, respectively. It can be seen that the positive electrode material has a high charge and discharge capacity, and the coulombic efficiency can reach 100%.

[0081] Figure 4 and Figure 5 The long cycle performance test diagram of the sodium ion half-cell prepared by the positive electrode material of Example 9 at 1C and 10C. The results show that the initial charge / discharge specific capacity of Example 9 is 122.8 and 122.6 mAh / g. After 200 cycles, the charge / discharge specific capacity is 106.3 and 106 mAh / g, and the capacity retention rate is 86.5%; in addition, after 500 cycles at a high current of 10C, the charge and discharge specific capacity is 78.9 and 78.6 mAh / g, and the capacity retention rate can still reach 91.6%.

[0082] Figure 6 and Figure 7 The cyclic voltammograms of sodium ion half-cells prepared from the positive electrode materials of Example 9 and Example 11 at scan rates of 0.1 mV / s and 1 mV / s, respectively. The results show that both the materials of Example 9 and Example 11 present six pairs of redox peaks, which is consistent with the sodium ion storage mechanism during the charge and discharge process of the tunnel-type manganese-based oxide.

[0083] Figure 8 and Fig. 9 The capacity-voltage curve diagram of the sodium ion full battery prepared from the positive electrode material of Example 9 at 0.1C and the long cycle performance diagram at 1C are respectively. The results show that the charge / discharge specific capacity of the sodium ion full battery at 0.1C is 119.2mAh / g and 115.2mAh / g, respectively. The initial charge / discharge specific capacity at 1C is 92.9mAh / g and 92.7mAh / g, respectively. Moreover, after 100 cycles, the charge / discharge specific capacity is 66.9mAh / g and 66.7mAh / g, the capacity retention rate reaches 72%, and the coulombic efficiency is 100%. This shows that the battery positive electrode material has high capacity and long cycle stability.

[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An ion-synergistic high-performance sodium ion battery cathode material, characterized in that: Its molecular formula is Na x Mn 1-y T y O 2- z N z , wherein: T and N are nickel and fluorine elements respectively; 0.44≤x≤0.6, 0≤y≤0.3, 0≤z≤0.3, and y and z are not 0 at the same time.

2. The method for preparing the ion-synergistic high-performance sodium ion battery positive electrode material according to claim 1, characterized in that: The steps include: (1) According to the Na x Mn 1-y T y O 2-z N z Weigh the sodium source, manganese source, T source and / or N source according to the atomic ratio of Na, Mn, T and / or N elements in the mixture; then dissolve the raw materials in an acidic solution and stir to react, separate the formed coprecipitated compound, dry it, and grind it to obtain a precursor for later use; (2) Sintering the precursor in an oxygen-containing atmosphere to obtain the positive electrode material.

3. The method for preparing the ion-synergistic high-performance sodium ion battery positive electrode material according to claim 2, characterized in that: In step (1), the sodium source includes one or more of sodium carbonate, sodium acetate, sodium nitrate, sodium acetate, sodium oxalate, and sodium citrate; preferably, 5-10% of the mass of the sodium source is added to the sodium source.

4. The method for preparing the ion-synergistic high-performance sodium ion battery positive electrode material according to claim 2, characterized in that: In step (1), the manganese source includes one or more of manganese sulfate, manganese acetate, manganese nitrate, and manganese acetate.

5. The method for preparing the ion-synergistic high-performance sodium ion battery positive electrode material according to claim 2, characterized in that: In step (1), the T source and the N source include one or more of nickel nitrate, nickel sulfate, nickel acetate and sodium fluoride.

6. The method for preparing the ion-synergistic high-performance sodium ion battery positive electrode material according to claim 2, characterized in that: In step (1), the acidic solution comprises one or more of acetic acid and oxalic acid; optionally, the concentration of the acidic solution is 1-5 mol / L, and the ratio of each raw material to the acidic solution is 1 g: 10-30 mL.

7. The method for preparing the ion-synergistic high-performance sodium ion battery positive electrode material according to claim 2, characterized in that: In step (1), the stirring reaction temperature is 50-80° C., and the reaction time is 4-6 hours; optionally, the stirring rate is 120-500 rpm / min.

8. The method for preparing an ion-synergistic high-performance sodium-ion battery positive electrode material according to claim 2, characterized in that: In step (1), the drying temperature is 100-120°C and the drying time is 8-12 hours; Optionally, in step (1), the grinding speed is 200-450 rpm / min, the time is 0.2-2 h, and the ball-to-material ratio is 13-26:

1.

9. The method for preparing the ion-synergistic high-performance sodium ion battery positive electrode material according to any one of claims 2 to 9, characterized in that: In step (2), the sintering treatment is carried out at a temperature of 700-1000°C and a time of 1-20 hours; Optionally, in step (2), the oxygen-containing atmosphere includes air.